Child-Care Costs and Mothers' Employment Rates. An Empirical Analysis for Austria - Helmut Mahringer; Christine Zulehner (Austrian Institute of Economic Research (WIFO), 2012)
The availability of affordable institutional child-care is increasingly discussed as an important determinant of the labour force participation of parents, particularly of mothers. This paper examines the impact of child-care costs on the employment rates of mothers with children younger than 15 years. Using data from the 1995 and 2002 Austrian Microcensus, combined with wage information from Austrian tax records, we estimate the impact of net wages and child-care costs on mothers' employment probabilities. In line with theoretical considerations and most of the international sub-literature, we find a negative elasticity of mothers' employment rates to child-care costs as well as positive elasticity with regard to wages. The point estimates for the impact of net-wages and child-care costs are of similar absolute size. Additionally, empirical results indicate that higher family income (without the earned income of the mother) reduces the employment probabilities of mothers.
Keywords: 330; Kinderbetreuung; Erwerbstätigkeit; Mütter; Familie-Beruf; Österreich